2021
DOI: 10.11591/ijeecs.v23.i2.pp752-759
|View full text |Cite
|
Sign up to set email alerts
|

A smart management system of electric vehicles charging plans on the highway charging stations

Abstract: Electric vehicles (EVs) are seen as one of the principal pillars of smart transportation to relieve the airborne pollution induced by fossil CO2 emissions. However, the battery limit, especially where the journey is with a long-distance road remains the most formidable obstacle to the large-scale use of EVs. To overcome the issue of prolonged waiting charging time due to the large number of EVs may have a charging plan at the same charging station (CS) along the highway, we propose a communication system to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…This analysis is crucial for developing targeted marketing strategies and improvement plans, ensuring sustainable utilization and enhancement of these resources. Many studies on improving the charging pile service have been carried out from different perspectives, such as satisfying the ever-growing demand for the charging service by predicting the number of charging piles needed [4]- [7], finding an appropriate location for charging station construction to form an efficient charging station network [8]- [12], improving the quality and convenience of charging service by building predictive models or organizational architectures to optimize the queuing time [13]- [14], and improving the efficiency of maintenance work by using algorithms to diagnose and detect faulty of charging piles [15]- [17]. These studies have achieved fruitful results in improving the charging pile service by exploring anticipatory planning.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis is crucial for developing targeted marketing strategies and improvement plans, ensuring sustainable utilization and enhancement of these resources. Many studies on improving the charging pile service have been carried out from different perspectives, such as satisfying the ever-growing demand for the charging service by predicting the number of charging piles needed [4]- [7], finding an appropriate location for charging station construction to form an efficient charging station network [8]- [12], improving the quality and convenience of charging service by building predictive models or organizational architectures to optimize the queuing time [13]- [14], and improving the efficiency of maintenance work by using algorithms to diagnose and detect faulty of charging piles [15]- [17]. These studies have achieved fruitful results in improving the charging pile service by exploring anticipatory planning.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have also proposed a strategy to mitigate the impact of future unknown EVs charging demands caused by the dynamic change of traffic conditions on the roads in [23], [24]. Our method based on the dynamic change of the charging plans of all EVs that have a charging reservation, the updating charging plans are made at each impact in the CSs states due to a new EV charging request.…”
Section: Introductionmentioning
confidence: 99%
“…IoT and cloud are utilized as a tool for energy management using SDN, through simulation at the consumer side [21]- [23]. Simulation studies are reported utilizing EV parameters for energy management [24]. An appropriate communication network is essential for the timely data exchange between EV sensors, EVCS and an energy control unit.…”
Section: Introductionmentioning
confidence: 99%